2018
DOI: 10.1177/0192512118779184
|View full text |Cite
|
Sign up to set email alerts
|

Education and trust: A tale of three continents

Abstract: To date, most research finds education to have a positive effect on trust. Education increases people’s social intelligence, making them better able to distinguish between trustworthy and opportunistic types. Alternatively, education allows people to attain privileged social status, making them more resistant to deceit and exploitation by opportunistic types. In this article we show that this is not always the case. The relationship between education and trust is mediated by state efficacy; where the state is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…In this study, I have considered how levels of trust differ across educational groups in different contexts globally. In line with recent cross-national studies (Borgonovi 2012;Charron and Rothstein 2016;Frederiksen, Larsen, and Lolle 2016;Güemes and Herreros 2019), my analysis of data from multiple sources, including three waves of the WVS, eight waves of the ESS, as well as country-level indicators from the World Bank, shows that the education and trust relation changes substantially both across countries and within countries over time.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In this study, I have considered how levels of trust differ across educational groups in different contexts globally. In line with recent cross-national studies (Borgonovi 2012;Charron and Rothstein 2016;Frederiksen, Larsen, and Lolle 2016;Güemes and Herreros 2019), my analysis of data from multiple sources, including three waves of the WVS, eight waves of the ESS, as well as country-level indicators from the World Bank, shows that the education and trust relation changes substantially both across countries and within countries over time.…”
Section: Resultssupporting
confidence: 80%
“…Similarly, Frederiksen, Larsen, and Lolle (2016) find that, whereas education has a positive impact on trust in low-corruption western democracies, it has a negative impact on trust in less developed and more corrupt societies, including Serbia, Turkey, Hungary, Slovakia, Bulgaria, Croatia, Kosovo, and Ukraine. Most recently, Cecilia Güemes and Francisco Herreros (2019) show that the association between education and trust is mediated by state efficacy: Whereas education has a positive impact on trust in Europe, it has a weak impact on trust in Latin America and a negative effect in Africa.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…They also say that the speed and the extent of changes are dependent on cultural inertia and elements of the given social environment, for instance changes in the social structure and political system. The nature of the effects of education on institutional trust is explained further in an empirical study by Güemes and Herreros (2018). These scholars show that the effect of education is dependent on state efficacy; in a weak state, educated people are less trusting, and alternatively, in those countries where state efficacy is higher, educated people tend to have more trust.…”
Section: Frameworkmentioning
confidence: 99%
“…Considering our theoretical objectives, however, we needed a sample biased in favor of greater diversity and unprejudiced reactions. As numerous studies have shown (e.g., Güemes and Herreros 2019; Thomsen and Olsen 2017), students and higher-educated individuals in consolidated democracies are high in social trust and disproportionately tolerant toward ethnic minority members. University students have an additional characteristic that suits our purposes: in democracies, universities recruit persons into the political and administrative elite, who often advocate lenient immigration policies, despite their unpopularity among lower-educated individuals (Thomsen and Olsen 2017).…”
Section: Data Measures and Experimental Designmentioning
confidence: 99%